Greater Inequality and Household Borrowing: New Evidence from Household Data. Issue 6 (6th January 2020) - Coibion, Olivier; Gorodnichenko, Yuriy; Kudlyak, Marianna; Mondragon, John
Abstract: Using household-level debt data over 2000–2012 and local variation in inequality, we show that low-income households in high-inequality regions (zip codes, counties, states) accumulated less debt relative to their income than low-income households in lower inequality regions. We also find evidence that low-income households face higher credit prices and reduced access to credit as inequality increases. We argue that these patterns are consistent with inequality tilting credit supply away from low-income households and toward high-income households, which may have long-run implications for outcomes like homeownership or entrepreneurship.